Peran Esensial Pendidikan Tauhid dalam Membangun Karakter Anti-Perundungan - Imam Mashudi Latif; Roikhatul Jannah (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
Abstract Bullying is a serious social and psychological problem in educational settings that demands fundamental preventive solutions. This study aims to analyze the essential role of tauhid education—a fundamental foundation of Islamic teachings that affirms the oneness of Allah Swt.—in developing anti-bullying character. Using a qualitative-descriptive approach, this article describes how the core values ​​of tauhid, such as the belief in the equality of all human beings before Allah and the awareness of divine supervision (muraqabah), effectively protect individuals from oppressive behavior. The analysis shows that tauhid fosters empathy, eliminates arrogance, and provides mental resilience for victims. Integrating the principles of tauhid and morals into the curriculum and school culture is key to creating a safe educational environment. Keywords : tauhid education, anti-bullying, student character, noble morals.